Creativity, Innovation and Promotion Variables as Determinants of Culinary Bussiness Success in OKU Regency - Sari, Yunita; -, Munajat; Permatasari, Fifian (Jurnal Manajemen, 2021)
The objective of this research was to examine the effects of creativity, innovation, and promotion variables as determinants of culinary business success in the Ogan Komering Ulu (OKU) regency. The research design was survey research with a quantitative approach. The population of this research consisted of culinary businesses in the OKU regency. The analytical method used was multiple regression. The conclusion of this research showed that creativity, innovation, and promotion variables had significant effects on the success of the culinary business in the OKU regency. This research focused on creativity, innovation, and promotion as independent variables and business success as the dependent variable